Atuante das mídias: o ator como linguagem na comunicação mediada - Silva, Regiane Caminni Pereira da (2007)
This thesis addresses the issue of representation as a performative language agent in the media communication genres. The main objective is to understand the semiosis of representation, not limited to the artistic context, as well to propose an extension and expansion of the communicative context. This study focuses on productions that configure performers, news casters, commercial and advertising actors, and well-known media characters as media agents, in contemporary Brazilian culture between 1999 and 2007, among the entertainment, news, and advertising genres. This work distinguishes between media agents produced for the media market and those processed by cultural relations. One of the primary assumptions of this work is that television is the privileged paradigm that defines other media, such as printed news media and non-mainstream media in that these media reflect the tele-visual paradigm. This work discusses the actor, fiction, parody and performance as modelling languages of the culture that configures the media agents. The issue is discussed under the approach of culture semiotics, according to studies from Tartu-Moscow School. The methodological procedure of this investigation focuses on the process of recodification based on the work Roman Jakobson and the modelling and cultural texts of Yuri Lotman and Boris Uspenskii. In regards to the theoretical foundation, the perception of the media as ambience is informed by Edgar Morin s theory of mass culture as well as the culture of media described by Lucia Santaella. Patrice Pavis, Marvin Carlson, Algirdas J. Greimas and Paul Zumthor are referenced to understand the actor and performer as language. The concept of the media agent as a hybrid of actor, performer and character, which can be positicioned in one or all three roles is essential for perceiving that in the media universe, we can find a product-agent or a process-agent. The first can degenerate the concept of actor, detrimental to the market demands. The second can be capable of promoting the cultural semiosis as well as valorizing the actor as language, emphasizing the importance of performance in communicative and cultural process